2019
DOI: 10.3390/pharmaceutics12010021
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte Membrane-Coated Arsenic Trioxide-Loaded Sodium Alginate Nanoparticles for Tumor Therapy

Abstract: Arsenic trioxide (ATO) has a significant effect on the treatment of acute promyelocytic leukemia (APL) and advanced primary liver cancer, but it still faces severe side effects. Considering these problems, red blood cell membrane-camouflaged ATO-loaded sodium alginate nanoparticles (RBCM-SA-ATO-NPs, RSANs) were developed to relieve the toxicity of ATO while maintaining its efficacy. ATO-loaded sodium alginate nanoparticles (SA-ATO-NPs, SANs) were prepared by the ion crosslinking method, and then RBCM was extru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 31 publications
1
19
0
Order By: Relevance
“…The encapsulated microcrystal did not grow to large crystal but was stabilized within microsphere for sustained release (Figure 2(A,D)). The drug load was over 40%, which is 5-6 folds higher than that of reported ATO-microspheres (Zhou et al, 2005(Zhou et al, , 2012 and 4-20 folds higher than that of reported ATO-nanoparticles (Yang et al, 2009;Ellison et al, 2017;Lu et al, 2018;Hu et al, 2019;Lian et al, 2019). The encapsulation efficiency was 21.6%, which was at the similar level as previously reported studies (Lu et al, 2018;Lian et al, 2019).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The encapsulated microcrystal did not grow to large crystal but was stabilized within microsphere for sustained release (Figure 2(A,D)). The drug load was over 40%, which is 5-6 folds higher than that of reported ATO-microspheres (Zhou et al, 2005(Zhou et al, , 2012 and 4-20 folds higher than that of reported ATO-nanoparticles (Yang et al, 2009;Ellison et al, 2017;Lu et al, 2018;Hu et al, 2019;Lian et al, 2019). The encapsulation efficiency was 21.6%, which was at the similar level as previously reported studies (Lu et al, 2018;Lian et al, 2019).…”
Section: Discussionsupporting
confidence: 75%
“…Nanoparticles and microspheres are effective tools for sustained drug delivery and multiple studies on ATO nanoparticles and microspheres have shown improved antitumor effects (Zhou et al., 2005 ; Yang et al., 2009 ; Zhou et al., 2012 ; Kalepu & Nekkanti, 2015 ; Akhtar et al., 2017 ; Ellison et al., 2017 ; Lu et al., 2018 ; Duan et al., 2019 ; Hu et al., 2019 ; Lian et al., 2019 ; Wu et al., 2020 ). The drug loading of ATO and its releasing pattern in these particles are essential for therapeutic efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…For longer circulation and less immune recognition of nanoparticle drugs, diverse strategies are reported, such as modifying the surface with polyethyleneglycol (PEG) or cell-penetrating peptides [ 22 ]. Among them, red blood cell membrane (RBCM), as a natural bio-membrane extracted from red blood cells (RBCs), attracted extensive attention as a drug carrier [ 23 , 24 , 25 ]. RBCM is expected to help achieve a long circulation of drugs because of the presence of special proteins like CD47 contributing to lower uptake by macrophages [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the administration of these drugs should be evaluated when beneficial effects outweigh metal toxicity. The development of new strategies employing the use of As-based drugs in coated NPs systems provides a promising alternative for safe and effective tumor treatment (Lian et al 2019). However, consideration of the individual genetic predisposition, co-exposure to other toxins, diet, and particularly vulnerable neurological conditions should be taken carefully into account in prescribing these treatments ).…”
Section: Use Of Arsenic In Medicinementioning
confidence: 99%